Peningkatan Keterampilan Menyampaikan Arahan Teks Prosedur Dengan Metode Project Based Learning (Pjbl) Melalui Media Instagramreels - Amalia Firdausa; Sintowati Rini Utami; Yantia Elestisa Lumbantobing (Peneliti.net, 2023)
This research is a classroom action research with the aim of improving students' speaking skills using the Project Based Learning method through Instagram reels media. The subjects of this study were 35 class VII D students of SMP Negeri 7 Jakarta. This research was conducted for three cycles with the stages of each cycle as follows (1) planning, (2) implementation, (3) observation, and (4) reflection. The data collection technique used in this study was by using observation sheets for students' speaking skills activities and speaking skills tests. The results showed an increase in the average value of students' speaking. The average value obtained in cycle 1 with a percentage of 52.85% is in the